2016
DOI: 10.3390/e18120453
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Citizenship Behavior and Sustainability in Urban Organizations: Towards a Theoretical Model

Abstract: Entropy is a concept derived from Physics that has been used to describe natural and social systems' structure and behavior. Applications of the concept in the social sciences so far have been largely limited to the disciplines of economics and sociology. In the current paper, the concept of entropy is applied to organizational citizenship behavior with implications for urban organizational sustainability. A heuristic is presented for analysing personal and organizational citizenship configurations and distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…Findings of OCB empirical studies [20,21], suggest that balance between personal and organizational goals in organizational citizenship is necessary for good organizational performance and that extremes of either a personal or organizational orientation may increase the propensity for organizational deconstruction. From the theoretical point of view, it is maintained in in line with Coldwell [2], that increasing amounts of either personally or organizationally oriented OCB which is distributed unequally amongst categories of organizational personnel will result in increases in in organizational deconstruction In the original model proposed by Coldwell and Callaghan [22], it was suggested that, at very high levels of personally oriented citizenship behaviour and very low levels of organizationally oriented citizenship behaviour ECB will occur. However, the heuristic is unable to articulate formally the distribution of personal and organizational citizenship behaviour that leads to ECB.…”
Section: The Concept Of Organizational Citizenship Entropymentioning
confidence: 96%
See 1 more Smart Citation
“…Findings of OCB empirical studies [20,21], suggest that balance between personal and organizational goals in organizational citizenship is necessary for good organizational performance and that extremes of either a personal or organizational orientation may increase the propensity for organizational deconstruction. From the theoretical point of view, it is maintained in in line with Coldwell [2], that increasing amounts of either personally or organizationally oriented OCB which is distributed unequally amongst categories of organizational personnel will result in increases in in organizational deconstruction In the original model proposed by Coldwell and Callaghan [22], it was suggested that, at very high levels of personally oriented citizenship behaviour and very low levels of organizationally oriented citizenship behaviour ECB will occur. However, the heuristic is unable to articulate formally the distribution of personal and organizational citizenship behaviour that leads to ECB.…”
Section: The Concept Of Organizational Citizenship Entropymentioning
confidence: 96%
“…The model suggested by Coldwell [2] points to a specific type of interaction, that of extreme organizational citizenship behavior, that can be seen in toxic employee citizenship-type behavior (i.e. behavior that goes the extra unwanted mile), that can lead to team deconstruction and ultimately undermine organizational survival.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the information which can be obtained from the dynamics of entropy functional is well recognized. An overview and critical analysis of possible entropy applications are presented in [19], known applications refer, as possible examples, to biological systems [20], social and financial markets [21,22], learning dynamics [23], dispersion or aggregation in human crowds, and vehicular traffic [24].…”
Section: Introductionmentioning
confidence: 99%
“…To characterize a given set of approaches the main features are included, especially distinguishing a given set. The set of indicators points out of the activities referring to evaluation of a degree of products [85], operations [43], whereas the set of measures emphasizes the basic background of measurements, including production [49] or processes [62]. Generally, the framework's aim is to ensure the guideline of how to integrate different sustainability aspects [86], assisting selected processes [12], or supplying sets of specified indicators for a given purpose [1].…”
mentioning
confidence: 99%
“…Some environmental attributes (i.e., resource usage, emissions waste and effluents) are considered by indicators [43,66]. This set also reveals the details of the form of description (i.e., qualitative and quantitative indicators) [12] and purpose (i.e., fundamental, general and leading indicators) [85]. The framework's types encompass the knowledge about more specified attributes, directly referred to the applied field, i.e., material stage, manufacturing stage, use stage [15], transport, energy use [93], or supply chain management [86].…”
mentioning
confidence: 99%